(untitled) - Farb, Peter (New York, 1978)
The publication of this book in 1968 marked the first comprehensive examination of the history and culture of native Americans. Today this work continues to stand as one of the major summaries of the indigenous societies of North America with its explication of such universal subjects as monotheism, war, capitalism, and sex.
Keywords: Indians of North America,Người da đỏ ở Bắc Mỹ